Development of ultra low formaldehdye emission particleboard using a new melamine-fortified urea formaldehyde resin - Lee, Seng Hua (2013)
An ultra low formaldehyde emission melamine-fortified urea formaldehyde (UF) resin with formaldehyde to urea molar ratio (F/U) as low as 0.88 was developed. Melamine- fortified resin yields a lower pH drop after addition of the hardener than UF resin and also causes a decrease of the hardening rate of the resin and, therefore, a lengthening of the hot press time is necessary. This study aimed to establish the optimum processing parameters to work with this resin in order to produce particleboard with formaldehyde emission and properties that comply with Japanese Industrial Standard (JIS). The processing parameters consist of shelling ratio of particles, pressing time and temperature. The tests for physical and mechanical properties were conducted in accordance with JIS A 5908:2003. Rubberwood served as the main raw material in this study. Oil palm trunk was used in the first stage of the experiment to examine its feasibility as an alternative raw material to replace conventional rubberwood. However, utilization of oil palm trunk failed to show convincing results. The ratio of 60% surface particles and 40% core particles showed the best result in MOR and TS for the particleboard produced. The newly-developed resin worked well under pressing temperature of 180°C for 270 seconds. Despite the satisfied mechanical properties, particleboard made with this resin showed poor dimensional stability and failed to meet the JIS requirement. Optimization with different wax content and resin usage level was carried out to impart better dimensional stability upon the particleboard. The predicted values were obtained by running optimizer with the desirability function chosen to minimize the TS value. Based on the prediction results, the required TS value can be achieved by the application 1.47% of wax and 10:13% of resin which seem not practical from economic point of view. In addition, further addition of wax exceed 1% did not bring any worthwhile improvement on the dimensional stability of the particleboard. Regarding to the matter, heat treatment was carried out with intention to improve the dimensional stability of particleboard. Two treatment methods with treatment temperature ranged from 100°C to 200°C were conducted. Significant reduction in TS value occurred starting from the treatment temperature of 160°C with the methods involved re-press process. Finally, particleboard complied with all criterions stated in JIS A 5908:2003 was successfully produced by the combination of wax and resin optimization along with the heat treatment.